Will QE change the dependence between Baht/Dollar exchange rates and price returns of AOT and MINT? - T. Kiatmanaroch (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This paper used the C-vine copula model to analyze the dependence between the returns of the Baht/Dollar exchange rates, and two stock prices in the travel and tourism sectors of the stock market of Thailand, under the second round and the third round of quantitative easing programs (QE2 and QE3). The results show that the degree of dependence which is measured by Kendall's tau correlation between the Baht/Dollar exchange rates, and the stock prices of AOT and MINT under the QE2 program is stronger than under the QE3 program.